STRATEGI GREEN MARKETING MIX PADA AGROINDUSTRI KOPI BIJI SALAK (KOPLAK FOOD) DI KECAMATAN AJUNG KABUPATEN JEMBER - rizki, sella; Kantun, Sri; Tiara, Tiara (Universitas Jambi, 2023)
The purpose of this research is to describe the implementation of the green marketing mix strategy in the Koplak Food Agroindustry. This research is a descriptive qualitative research. The author conducted interviews, observations and documentation to collect data. The data analysis technique used is the data analysis technique of Miles and Huberman. The result of this research is the application of green marketing mix on green product indicators indicated by organic products and during the manufacturing process while maintaining cleanliness. The application of Green price can be shown by setting a relatively more expensive price, but the price is in accordance with the quality of the product. The application of a green place can be seen that the production house is always kept clean. The application of green promotion is that the promotion is carried out in a transparent and educative manner through exhibitions and promotional media owned. Koplak Food's agroindustry has not included a logo on environmental friendliness on the packaging, namely eco label and eco brand. So the recommendation that can be given is to immediately register for ISO 14001 certification in order to be able to provide an environmentally friendly logo on the packaging.